Examining the behavior of credit rating agencies post 2008 economic turmoil - Çağrı L. Uslu (International Journal of Management and Economics, 2017)
The demand for sovereign ratings has increased throughout last decades. Until the1990's, credit rating agencies (CRAs) did not rate most of the emerging markets and the focus was almost only on developed countries, however, during this decade the number of sovereigns rated increased dramatically due to addition of emerging markets to the portfolio. The global financial crisis in 2008 led to the loss of credibility of these major credit rating companies. None of these three agencies showed any signal of macroeconomic problems in countries where the financial crisis created devastating macroeconomic results. It is believed that this failure has led credit rating agencies to behave more conservatively. This paper aims to determine whether CRAs tend to behave conservatively after the 2008 global financial crisis. If the downgrading is greater than the worsening of the economic situation in the given economies, then we can infer that CRAs tend to behave more conservatively. The good working model in estimating ratings assigned by CRAs before the crisis failed to estimate the ratings after 2008 crisis. This may have happened due to two reasons. First, as experienced in the aftermath of the former crisis, credit rating agencies may have added new macroeconomic variables in the process of assigning ratings or change the weight assigned to the already existing macroeconomic variables. Second, it is a known fact that ratings emerge from the combination of two distinct information; the quantitative part reflected by macroeconomic indicators and the qualitative judgements of the agency about the sovereign.
Keywords: F34; F63; E44; E47; 650; Credit Rating Agencies; 2008 economic crisis; Turkey